PENGARUH METODE TOKEN TOKEN EKONOMI TERHADAP PENINGKATAN KEDISIPLINAN ANAK KELOMPOK A DI TK KREATIVA MATARAM - Dian Nazila; Muazar Habibi; Ika Rachmayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine whether there is an influence of thetoken economy method on improving the discipline of group A children atKindergarten Kreativa Mataram. In the Kindergarten Kreativa, positive behavior isreinforced in children by giving rewards in the form of verbal awards, namely praisefrom teachers. Awards are not only verbal, but there are also non-verbal ones, oneof which is with economic tokens. Therefore, in-depth research is needed to identifythe extent to which this token economy method can be effectively applied in thecontext of this preschool education. The approach used in this study is a quantitativeapproach with the type of research used, namely Quasi-experimental: One-GroupPretest-Posttest design, which is a group measured and observed before and aftertreatment. The data collection technique used is the Observation method using aLikert scale and documentation methods. The subjects of this study were 11 childrenin group A at Kindergarten Kreativa Mataram. The results of the pre-test beforegiving economic token treatment, discipline in children was 39.81% and after givingeconomic token treatment, the level of discipline in children increased to 80.27% soit can be concluded that there is an influence of the economic token method onincreasing the discipline of group A children at Kindergarten Kreativa Mataram.